Psychological traits and purchase intention in Lebanese aesthetic clinics: The mediating role of brand attitude - Kabbout, Rabih; Abbas, Alaa (Edelweiss Applied Science and Technology, 2026)
This paper investigates how value consciousness, susceptibility to normative influence, and consumer need for uniqueness shape purchase intention in Lebanese aesthetic clinics, and whether brand attitude mediates these relationships. A structured questionnaire was administered to 350 current or potential users of aesthetic clinic services in Lebanon. Data were analyzed using SPSS 27 and AMOS 27 through reliability and validity tests, correlation analysis, structural equation modelling, and bootstrapped mediation analysis. Value consciousness, normative influence susceptibility, and consumer need for uniqueness positively influenced both brand attitude and purchase intention. Brand attitude also has a strong positive impact on purchase intention and partially mediates the relationships between the three psychological traits and purchase intention. The findings indicate that both functional and symbolic assessments influence clinic choice in the Lebanese context, where economic strain, social signaling, and identity expression occur concomitantly. Aesthetic clinics should strengthen value-based positioning, use socially credible communication, and offer differentiated brand experiences that appeal to value-seeking, socially influenced, and uniqueness driven consumers.